Construction of a HSC activation-related lncRNA–miRNA–mRNA ceRNA regulatory network reveals potential molecules involved in liver fibrosis - Wan, Kaiqiang; Zhou, Qiong; Feng, Ruirui; Liu, Tao; Fan, Chang; Pang, Xue; Li, Zhongliang; Zhou, Qiumei (Frontiers in Genetics, 2025)
BackgroundLiver fibrosis (LF) represents a progressive pathophysiological consequence of persistent liver injury. Although the competitive endogenous RNA (ceRNA) network serves as a critical regulator in diverse disease pathogenesis, its molecular underpinnings in LF and fibrogenic mediators remain unknown.ObjectiveIn this study, we aimed to systematically probe the LF-related ceRNA regulatory axis and identify the potential molecules involved in the activation of hepatic stellate cells (HSCs).Methods and ResultsBased on the whole transcriptome RNA sequencing, 401 lncRNAs, 60 miRNAs, and 1,224 mRNAs were identified between model and normal liver tissue samples. Then, through target gene prediction, an lncRNA–miRNA–mRNA (LMM) ceRNA network comprising four differentially expressed lncRNAs (DE lncRNAs), six DE miRNAs, and 148 DE mRNAs was established. The expression levels of these RNAs were verified by RT-qPCR. Functional annotation via the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed that target mRNAs of co-dysregulated lncRNAs and miRNAs in model groups were significantly enriched in multiple pathways, such as unsaturated fatty acids and TGF-β signaling pathways. Notably, four hub mRNAs (HMGCR, SREBF-1, TGF-β3, and FBN1) were identified by constructing a protein–protein interaction (PPI) network with the 148 DE mRNAs. Importantly, the dual-luciferase reporter assay confirmed the existence of specific binding sites among lncRNA H19, miR-148a-3p, and FBN1. Finally, the gene expression levels were verified by RT-qPCR in TGF-β1-induced JS-1 cells, revealing that five lncRNA–miRNA–mRNA relationship pairs containing H19, miR-130a-3p, miR-148a-3p, TGF-β3, FBN1, and HMGCR were involved in the activation of HSCs.ConclusionIn this study, an HSC activation-related ceRNA network was successfully established in mice liver tissue, which could provide a novel framework for elucidating pathogenic mechanisms and identifying clinically relevant prognostic markers in LF progression.